Framing Effects on Online Security Behavior - Rodríguez-Priego, Nuria; van Bavel, René; Vila, José; Briggs, Pam (Frontiers in Psychology, 2020)
We conducted an incentivised lab experiment examining the effect of gain vs. loss-framed warning messages on online security behaviour. We measured the probability of suffering a cyberattack during the experiment as the result of five specific security behaviours: choosing a safe connection, providing minimum information during the sign-up process, choosing a strong password, choosing a trusted vendor, and logging-out. A loss-framed message led to more secure behaviour during the experiment. The experiment also measured the effect of trusting beliefs, cybersecurity knowledge and gender. Trusting beliefs had a negative effect on security behaviour, cybersecurity knowledge had a positive effect, and gender had no significant effect.